2013
DOI: 10.3138/ptc.2012-06
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Exercise Therapy in Reducing Shoulder Pain Related to Breast Cancer: A Systematic Review

Abstract: Purpose: Recent research indicates that physiotherapy interventions, such as exercise and manual therapy, may be effective in decreasing the frequency of side effects linked with breast cancer treatment, including fatigue, pain, nausea, and decreased quality of life. This systematic review aims to determine the efficacy of exercise therapy in reducing shoulder pain related to breast cancer treatment and to identify outcome measures that can be used to assess shoulder pain in this population. Methods: A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
5
38
0
2
Order By: Relevance
“…Tatham et al reported that different face‐to‐face interventions were effective at reducing shoulder pain after intervention and follow‐up in patients with BC. Our pain‐related results were similar to those reported by Tatham et al using a nonface‐to‐face intervention but targeting the same parameters in general terms. Our findings related to static and dynamic muscle strength variables are in agreement with the literature describing traditional interventions in cancer survivors with regard to both intervention effects and maintenance effects .…”
Section: Discussionmentioning
confidence: 99%
“…Tatham et al reported that different face‐to‐face interventions were effective at reducing shoulder pain after intervention and follow‐up in patients with BC. Our pain‐related results were similar to those reported by Tatham et al using a nonface‐to‐face intervention but targeting the same parameters in general terms. Our findings related to static and dynamic muscle strength variables are in agreement with the literature describing traditional interventions in cancer survivors with regard to both intervention effects and maintenance effects .…”
Section: Discussionmentioning
confidence: 99%
“…Secondarily, Tatham and colleagues acknowledged inconsistencies with respect to pain outcome measures: four of the six included studies used a visual analogue scale (VAS), one of which also used the Brief Pain Inventory (BPI), while the other two studies relied solely on oral selfreports of pain. 1 Pain is a dynamic experience that may not be adequately captured by a clinician at any one time point. In addition, unidimensional assessments of pain such as VAS may not be effective in identifying different types and origins of pain and may be unable to tease out multiple pain sources.…”
mentioning
confidence: 99%
“…Tatham and colleagues' article also recognizes that not all pain outcome measures in common use are able to properly capture, qualify, and/or measure pain in this population. 1 Tatham and colleagues conducted a multi-database search and obtained results from six studies examining patients with breast cancer who underwent physiotherapy intervention, which they reviewed systematically to determine the efficacy of these interventions in reducing shoulder pain. 1 The interventions analyzed in these studies included varying combinations of shoulder/scapular strength and stability exercises, posture education, massage, ROM, general conditioning exercises, and/or lymphedema management.…”
mentioning
confidence: 99%
See 2 more Smart Citations